2010
DOI: 10.1007/s00256-010-0999-9
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of fibrous dysplasia of bone mimicking skeletal metastasis on 18F-FDG PET/CT imaging

Abstract: In our study, FDB had wide skeletal distribution with variability of 18F-FDG uptake and CT appearance. SUV in the delayed stage was seen to either decrease or increase on dual-time 18F-FDG PET scanning. It is very important to recognize the characteristics of this skeletal dysplasia to allow differentiation from skeletal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
42
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 17 publications
0
42
2
Order By: Relevance
“…The ability of Na 18 F PET/CT to detect skeletal metastases has been evaluated in various types of cancer, including prostate cancer, and a series of studies has reported improved sensitivity and specificity compared with 99m Tc-BS (7)(8)(9)(10)(11)(12)(13). In 2011, the Food and Drug Administration approved a new-drug application for Na 18 F PET/CT from the National Cancer Institute; however, its routine clinical use is not yet defined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of Na 18 F PET/CT to detect skeletal metastases has been evaluated in various types of cancer, including prostate cancer, and a series of studies has reported improved sensitivity and specificity compared with 99m Tc-BS (7)(8)(9)(10)(11)(12)(13). In 2011, the Food and Drug Administration approved a new-drug application for Na 18 F PET/CT from the National Cancer Institute; however, its routine clinical use is not yet defined.…”
mentioning
confidence: 99%
“…99m Tc-methylene diphosphonate bone scanning ( 99m Tc-BS) is currently the most widely used method for detecting bone metastasis; however, Na 18 F PET combined with CT has higher sensitivity and specificity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, similar to bone scintigraphy, benign bone conditions can also show increased 18 F-FDG uptake on PET-CT, and PET-positive asymptomatic fibrous dysplasia can be misinterpreted as a metastasis [4]. Fibrous dysplasia of bone has wide skeletal distribution, with variability of 18 F-FDG uptake and CT appearance [5,6]. It is therefore important to recognize the characteristics of this skeletal dysplasia, to allow differentiation from skeletal metastasis [6,7].…”
mentioning
confidence: 99%
“…Fibrous dysplasia of bone has wide skeletal distribution, with variability of 18 F-FDG uptake and CT appearance [5,6]. It is therefore important to recognize the characteristics of this skeletal dysplasia, to allow differentiation from skeletal metastasis [6,7]. Bone lesions with 18 F-FDG uptake need to be carefully interpreted when evaluating patients with known malignancy [8].…”
mentioning
confidence: 99%